Small business under sanctions - A. Yu. Yanchenko; M. M. Repilova (Путеводитель предпринимателя, 2025)
This work is devoted to the analysis of the specifics of the functioning of small and medium–sized enterprises in Russia. The conducted research allowed to identify the negative consequences caused by economic sanctions, as well as to identify key measures of state support for entrepreneurial activity.